Wireless Communication Using Embedded Microprocessor-5G Embedded E-Commerce System Oriented to Fruit Ordering, Sales, and Logistics - Chen, Tung-Chun; Liang, Yu-Shen; Ko, Po-Sheng; Ho, Ping-Tsan; Huang, Jui-Chan (Wireless communications and mobile computing, 2022)
With the birth of the Internet, information and data can flow in both directions, and, after that, it has spread to thousands of households. On this basis, e-commerce was also born, and it took a very short time from the field that no one cared about at the beginning to the hot focus field now. The development of e-commerce has broadened the sales channels of farmers, which has further increased the sales benefits of fruits and other agricultural products, conformed to the development of the times, and further supplemented the sales of fruits and other agricultural products. Based on the use of embedded microprocessors, this paper constructs an e-commerce system integrating sales and logistics. Based on the logistics model in the e-commerce platform, an e-commerce logistics identification model is constructed to measure the e-commerce logistics service level of agricultural products such as fruits. The article analyzes the sales and transportation methods of fruits and other agricultural products. Through a detailed analysis of the traditional e-commerce system, the e-commerce sales system has been optimized and improved by combining the reference cases and the data obtained from the Internet, especially in the aspect of logistics transportation. According to the data experiments in this article, it is shown that, after using the data formula for calculation, the best plan for transporting fruits and other agricultural products can be obtained. In the calculation result of the formula, the cost of delivery without considering customer satisfaction is 586 yuan, and the average delivery time of the vehicle is 5.625 hours, but the average satisfaction is only 78.5%. Compared with customer satisfaction, although the cost is about 15 yuan more and the delivery time is a few minutes longer, the customer satisfaction is about 21% higher than the customer satisfaction without considering the customer. Based on the optimized and transformed e-commerce system, this article will further improve the e-commerce platform for fruits and other agricultural products.